Microorganisms present in artisanal fermented food from South America - Jimenez, Maria Eugenia; O’Donovan, Ciara M.; Ullivarri, Miguel Fernandez de; Cotter, Paul D. (Frontiers in Microbiology, 2022)
Artisanal fermented products (foods and beverages) are produced in an artisanal way in many countries around the world. The main purpose of fermentation is to preserve the food, improve its safety, increase the nutritional and health-promoting value, and add specific flavours. In South America, there is a great variety of fermented food produced in an artisanal way. Different raw materials are used such as potatoes, sweet potato, cassava, maize, rice, milk (cow, ewe, goat), and meat (beef, goat, lamb, llama, and guanaco). Some of these fermented foods are typical of the region and are part of the culture of native communities, e.g., tocosh, masa agria, puba flour, charqui, chicha, champu, and cauin among others (indigenous foods). However, other fermented foods produced in South America introduced by mainly European immigration, such as cheeses and dry sausages, and they are also produced in many different parts of the world. In this work, the microbial composition of the different artisanal fermented products produced in South America is reviewed, taking into consideration the associated raw materials, fermentation conditions, and methodologies used for their production.